Picturing the barrio : ten Chicano photographers - Foster, David William (Latino and Latin American profiles, 2017)
Introduction; Part I. The Barrio: A Chicano Anchor; 1. Barrio Lives: Ricardo Valverde's East Los Angeles Photography; 2. Photography & Nostalgia: The Touched-Up Images of Kathy Vargas; 3. Los Angeles & Other Alien Lands: Harry Gamboa Jr.'s Photography of Urban Exile; 4. Barrios & the Visibility of Enduring Lives: Louis Carlos Bernal; Part II. Individual Subjectivities; 5. Woman's Body & Other Objects of Nature: The Nude Photography of Laura Aguilar; 6. On the Homosociality of Vatos: José Galvez; Part III. Chicano Cultural Perspectives.